Synthesis and characterization of SnO2-HMD-Fe materials with improved electric properties and affinity towards hydrogen. Issue 8 (June 2016) - Bouazizi, N.; Bargougui, R.; Boudharaa, T.; Khelil, M.; Benghnia, A.; Labiadh, L.; Ben slama, R.; Chaouachi, B.; Ammar, S.; Azzouz, A.
Abstract: Tin oxide (SnO2 ) was functionalized by hexamethylenediamine (HMD) grafting and incorporation of iron nanoparticles (Fe-NPs) and, then, fully characterized by X-ray diffractometry, transmission electron microscopy, diffuse reflectance spectrometry, FTIR spectrophotometery, photoluminescence spectroscopy and complexes impedance spectroscopy measurements. The covalent surface-grafting of HMD within mesopores was confirmed by the results from Fourier-transformed infrared spectroscopy. XRD and TEM study showed a dominant tetragonal structure. Fe-NPs were finely dispersed inside mesopores, producing a slight structure compaction. The crystallite size decreased in the presence of HMD and Fe-NPs. Photoluminescence (PL) insights revealed the presence of oxygen vacancies and the PL intensity was found to strongly depend on HMD grafting and Fe-NPs insertion. The incorporation of both Fe-NPs and HMD grafting appear to be responsible for electrical properties improvement. This material displayed an unprecedented surface affinity factor towards hydrogen of 8.5 μmol m −2 at ambient temperature and pressure. This was attributed to the contribution of both physical and chemical hydrogen adsorption, and to the presence of fine Fe-NPs. These properties open promising prospects for green energy storage. Graphical abstract: Synthetic strategy towards SnO2 -HMD-Fe for hydrogen storage.